Editorial: Origin of tropical diversity: From clades to communities (2016)
For centuries, one of the main questions in relation to the Earth’s biological diversity has been disentangling the causes for the comparatively high diversity in tropical zones, particularly the Neotropics. This volume aimed to demonstrate how molecular phylogenetics, phylogeography, paleontology, and paleoecology contribute to our understanding of the processes that gave rise diversity in the tropics. The response of authors to our initial invitation to participate was overwhelming, and the resulting manuscripts are brought together in this eBook. We have attempted to order the contributions, placing first those that deal with general conceptual or methodological issues and that are relevant to all parts of the tropics. These included studies on how tropical diversity was generated and/or is maintained at those local scales (Cannon and Lerdau; Beheregaray et al.; Collevatti et al.). The next group of articles focuses on specific taxa, though in most cases these are distributed throughout the tropics, and so address global questions. The final group of articles addresses studies confined to single major tropical regions including Africa and Australia.